Нормативно-правові аспекти визначення понять «соціальний захист» і «соціальне забезпечення» - Копетюк, М; Kopetiuk, M (СНУ ім. Лесі Українки, 2019)
Статтю присвячено аналізу нормативно-правового визначення ознак, змісту, сутності, юридичної природи та співвідношення понять «соціальний захист» і «соціальне забезпечення», які здійснюються від імені і за дорученням держави відповідними уповноваженими на це службовими і посадовими особами та органами й реалізуються у сфері правовідносин між громадянами й державою за допомогою спеціальних інститутів. Поняття «соціальний захист» і «соціальне забезпечення» слід сприймати як співвідношення цілого та його складової, яке стосується фактично усієї соціальної сфери в державі. The article is devoted to the analysis of the normative and legal definition of the specifics, content, essence, legal nature and the correlation between the concepts of «social protection» and «social security», which are carried out by the authorized officials, state servants and bodies on behalf of the state and are realized in the sphere of legal relations between citizens and the state through special institutions. The goal of the state social policy is to create conditions for the development and effective functioning of social relations, providing special protection to those groups of people who need it. The objects of social policy are the social and labor sphere, which characterize the degree of social development and reflect the unity and interdependence of labor and social relations. The subjects of the social policy are individuals and a social state. The right to social security is one of the most vital human rights formed in the course of a person's development in the society and which is recognized by the world community and secured in the international legal acts.
Definition of the Concepts of «Social Protection» and «Social Security»: Normative-Legal Aspect
Keywords: соціальний захист; соціальне забезпечення; інститути соціальниого захисту і соціального забезпечення громадян; social protection; social security; institutes of social protection and social security of citizens